Comparing In-Person and Remote Qualitative Data Collection Methods for Data Quality and Inclusion: A Scoping Review - Julie Roberts; Chinwe Onuegbu; Bronwyn Harris; Corinna Clark; Frances Griffiths; Kate Seers; Puren Aktas; Sophie Staniszewska; Felicity Boardman (International Journal of Qualitative Methods)
Background: In-person data collection has long been considered the ‘gold standard’ for qualitative data collection. Societal changes and the rapid increase in the use of remote methods during the Covid-19 pandemic intensified debate about the limitations and opportunities of remote data collection, while reigniting questions about data quality and inclusion. Objective: We sought to map available evidence exploring the characteristics and quality of remotely collected qualitative data compared to in-person qualitative data. Eligibility Criteria: A scoping review was conducted of empirical research studies that employed both remote and in-person methods with similar participants, to address the same research question. Sources of Evidence: Searches were conducted in MEDLINE, CINHAL, Web of Science, Scopus and Applied Social Science Index and Abstracts (ASSIA). The review includes peer reviewed articles published in English since 2000. Methods: Data were extracted from included papers using a data extraction tool based on JBI guidance, adapted to address our research questions. Results: A total of 58 articles are included. These cover a range of research methods and participant groups. Overall, remotely collected data is likely to generate similar themes to data collected in person but more concisely. Sensitive topics may be the exception. Non-verbal data and interaction between participants may be lost but the significance of this for data quality is not as well understood as participants may disclose more information remotely. Conclusions: Researchers should consider the fit of epistemology, population and topic when making decisions about remote data collection. If the benefits of remote data collection for qualitative research are to be fully realised, further research is needed to identify which elements of in-person and remote qualitative data collection are most effective, with which populations and research topics, and how remote data differs from in-person data.